Preparation for school art: young children's meaning making practices in out-of-school settings - Kriel, Benjamin (School of Education, 2015)
This thesis examines children’s meaning making with art related media in the home of a set of siblings, a brother and sister, of 8 and 6 years old respectively. It is argued that children’s meaning making with art related media is a self-sustaining, multimodal and dialogic site where family narratives, identity and childhood aims and intentions converge. It is argued that when art oriented adults, who seek to promote their child’s artistic growth, are sensitive to the dynamics of child meaning making, especially those that relate to play, they can achieve a more fruitful, aligned and relevant extension of these activities toward early art related goals. In order to make this argument material is presented from a lengthy session of play dough modelling involving the two children and their father, which includes dialogue surrounding this activity, and observations gleaned from video footage and written field notes. This thesis looks at how children’s meaning making in out-of-school settings, has elements of a distinct semiotic domain; not one where ‘art’ or art related media are the focus of the domain, but rather one where play and its affordances for certain kinds of child agency lead and shape the flow of meaning making. It is found that where the end product and pictorial qualities is not the focus of meaning making, and instead other communicative modes are given expression, such as imaginative and collaborative play, children’s interest is sustained as shared cultural resources are more easily integrated into the events.